PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP RISIKO INVESTASI DENGA PERATAAN LABA SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 HINGGA 2017 - Tri Winarti; Kamaliah Kamaliah; Azwir Nasir (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This research has some purpose there are to give empircal prooof about profitabilityand leverage an affect risk investment with mediating variable is income smoothing.The population in this study are all maufacturing companies listed in Indonesia StockExchange (BEI) in the period 2014-2017. This study has 252 observation withprobability method and purposive sampling technique. In processing data, StructuralEquation Modelling (SEM) is applied as data analysis technique. The result foundedthat profitability has not influence on risk investment, leverage has not influence onrisk investment, profitability has influence on income smoothing, leverage has notinfluence on income smoothing, income smoothing has influence on risk investment,the influence of profitability on risk investment is weaken by income smoothing.